Management of Madrasah Leadership - Andi Muhammad Ajigoena; Hisbullah Hisbullah (Kontigensi : Jurnal Ilmiah Manajemen, 2022)
This article discusses management of leadership in the madrasah environment. The main focus of this article is on the challenges faced by madrasah leaders in managing change and resistance from stakeholders. This research is a qualitative study that draws on practical experiences of leadership management in the madrasah environment. The case study approach can provide a detailed picture of the situations and challenges faced by madrasah leaders in managing change and resistance, as well as the strategies used to address them. In the case study, data can be obtained through interviews, observations, and document analysis to provide a more comprehensive picture of the case being studied. Through literature review and practical experiences, this article discusses several effective leadership management strategies for managing change and resistance in the madrasah environment. This article also discusses the importance of effective communication and participation from all relevant parties in the leadership management process in madrasah. This article is expected to contribute to the development of leadership management in the madrasah environment and strengthen the role of madrasah in shaping the character and personality of the younger generation. The results presented show that: First, school leadership management can respond to resistance from school communities by acting as a source of information, initiator of innovation programs, and agent/driving force in overcoming school community resistance to curriculum changes. Good school leadership management can help improve the quality of education in madrasahs, strengthen leadership positions inside and outside the school, and create a conducive and innovative working environment for teachers and school staff. Second, in order to overcome school community resistance to curriculum changes, visionary, participative leadership that is capable of initiating innovation programs is required. The school principal as a leader must understand the conditions and characteristics of the madrasah, be able to communicate clear and consistent vision and goals, and motivate teachers and school staff to work together in overcoming these challenges.